Structural correlates of high antibody affinity: three engineered amino acid substitutions can increase the affinity of an anti-p-azophenylarsonate antibody 200-fold. - Sharon, J (1990)
The basis for the 200-fold difference in affinity between two hybridoma antibodies specific for the hapten p-azophenylarsonate (Ars) that have diversified by somatic hypermutation was examined. Oligonucleotide-directed mutagenesis was used to sequentially convert the nucleotide sequence of the lower-affinity antibody into that of the higher-affinity one, and the mutant antibodies generated by transfection of hybridoma cells were analyzed for affinity to Ars-tyrosine. The data showed that out of the 19 amino acid differences between the two hybridoma antibodies, the affinity increase could be reproduced by three heavy-chain substitutions that are present in the high-affinity antibody. The combined effect on affinity of amino acid substitutions was generally found to reflect their individual effects. Although the light chain of the high-affinity antibody did not seem to play a major role in the affinity increase, its contribution varied with the kind and number of heavy-chain substitutions. The results hold promise for antibody engineering and are consistent with a stepwise acquisition of somatic hypermutations in which the existing structural context of an antibody most likely influences the affinity-based selection of later substitutions. They further suggest that many substitutions may be tolerated in vivo during the antigen-driven selection process, even though they confer on the antibody no affinity increase.